communication - بوزناد سميرة/bouznad samira (جامعة محمد بوضياف -المسيلة, 2026)
Summary The handout is a pedagogical course book designed for Master’s students. It explains the evolution of communication media from traditional forms to digital technologies and examines how these media influence learning, behavior, and society. Particular attention is given to educational contexts and psychometric assessment, highlighting the role of communication media in shaping teaching, learning, and evaluation practices. The course positions communication as a fundamental human phenomenon and a key driver of social interaction, knowledge exchange, and civilizational development. Intended for Master 1 students in Psychometrics and Educational Assessment, it aims to develop both theoretical and applied understanding of communication dynamics and media transformation in the digital era, with emphasis on their psychological and social implications. The handout introduces foundational concepts of communication, explaining how meaning is constructed through the interaction of sender, message, channel, receiver, and feedback. It also discusses the concept of “noise” and how it can disrupt understanding. In addition, it traces the historical evolution of communication, from early human expression and writing to printing, telecommunication, broadcasting, and contemporary internet-based interactive media. Different types of communication media are analyzed, including mass media such as radio, television, and advertising, as well as interpersonal and private media like the telephone, mobile phone, and messaging applications. The course presents criteria for classifying media—such as traditional versus digital, one-way versus two-way communication, number of participants, and sensory modes—emphasizing that the choice of medium directly affects communication effectiveness. A dedicated section focuses on the internet and digital transformation, addressing the nature of networks and key services such as search engines, email, social networks, chat platforms, databases, and distance learning. The handout links the expansion of digital media to major changes in education, particularly the rise of blended and distance learning and the growing importance of digital tools in teaching and assessment. Finally, the course analyzes the psychological and social effects of modern media use, including attention difficulties, problematic or addictive behaviors, anxiety, and identity-related challenges, as well as broader impacts on social relationships and community life. It concludes with a forward-looking perspective on future communication media, highlighting emerging technologies such as artificial intelligence and immersive environments, and raising ethical and social questions related to their use.